Effect of Photoperiod on Production of Ring-Necked Pheasants (Phasianus colchicus) - Alva, V.I.A.; Quintana , L.J.A.; Gonzales-Rebeles, I.C.; Gonzalez, A.M. (International Journal of Poultry Science, 2015)
This study assessed the effect of photoperiod duration on production parameters (amount of eggs and weight) in ring-necked pheasants (Phasianus Colchicus). Forty-five birds were caged, distributed in groups of one male and four females (total 9 cages). Three photoperiod treatments were applied (18, 16 and 14 h of light) with three repetitions per treatment. Males and females were randomly assigned to the different groups. An ANDEVA test was used to compare means between treatments, with a multiple comparison Tukey’s test in a GLM with SAS V.8.0. software package. Production parameters were recorded during 18 production weeks: egg weight (EW), egg mass (EM), eggs per female (EF) and laying percentage (LP). Significant differences were found in all variables between weeks (p<0.01), although the interaction of photoperiod with week was not significant (p>0.05). Photoperiod treatment had a significant effect on LP, EF and EM (p<0.05) during the study period (18 weeks); EW showed a 0.65% difference between the 18 h-light and 14 h-light treatments, although not statistically significant (p>0.05). All productive variables improved with the highest light-hours treatment (18 h) with the exception of EW.